Rendimiento agronómico de una variedad de rosa High Intense mediante técnicas de inducción floral manual y química, en San Isidro, cantón Espejo, provincia del Carchi - Pilacuan Hernández, Luis Antonio (2018)
VII. SUMMARY The investigation was carried out in the parish of San Isidro, Cantón Espejo, province of Carchi located at the following geographic coordinates of, 0º 56 'north latitude and 78 ° 25'54,4 "west longitude, with a height of 3000 masl, The climatological conditions of the area show an average annual precipitation of 600 mm, temperature 16 C ° and a relative humidity of 60%. The life zone is located in Montane Bajo dry forest (bs-MB). The objective of the research was to determine the agronomic performance of the variety of roses (Rosae sp) by manual floral induction techniques (pruning, overwhelm) and chemical (cytokinin, folic acid), given the low yields in an established 2-year crop. under greenhouse conditions. Seven treatments were evaluated combining the techniques of floral induction and the application of hormones Agobio, Agobio + cytokinin, Agobio + folic acid, Pruning, Pruning + cytokinin, Pruning + folic acid and an absolute Control with three repetitions total 21 treatments. Using the Design of Random Complete Blocks (DBCA). The evaluated variables were: number of viable buds, length of stem (60 DDPA), length of stem to cut, caliber of button to cut, yield and economic analysis of the treatments. From the results obtained it was determined that the most efficient floral induction technique in terms of production of longer stems was the Agobio. The combination of treatment 3 (Agobio + cytokinin) positively influenced the development of the crop, presenting a higher average in the evaluation of length. of stem, caliber of button, greater production in stems of 80, 90 and 100 cm and obtained the highest yield per hectare of 14,020.80 USD.